222Rn dose of mine water in different underground uranium mines. (July 2021) - Beg, Imran Athar; Sahu, Patitapaban; Panigrahi, Durga Charan
Abstract: This paper describes the method for estimation of the contribution of mine water to 222 Rn dose and its health risk using smart radon monitor with bubbler kit in Indian underground uranium mines. A significant positive correlation between 222 Rn release rate and the water flow rate was also established in this paper. The geometric means of 222 Rn doses in Mine 1 and Mine 3 were found to be 2.3 μSv y −1 and 9.6 μSv y −1, respectively. The arithmetic means of 222 Rn doses in Mine 2, Mine 4, and Mine 5 were found to be 4.9 ± 4.0 μSv y −1, 27.1 ± 20.2 μSv y −1 and 13.7 ± 2.6 μSv y −1, respectively. The mean values of 222 Rn doses in the above mines were well below the limit value of 100 μSv y −1 reported by the European Council. The average values of excess lifetime cancer risk (ELCR) in the mines varied from (5.9 ± 1.1) × 10 −3 to (70.0 ± 53.3) × 10 −3 . The mean 222 Rn-induced lung cancer cases per year per million persons (RnLCC) were found to be far below the limit range of 170–230 × 10 −6 recommended by the International Commission on Radiological Protection. Therefore, mine water was found to be less contributor to the 222 Rn dose in underground uranium mines. Highlights: 222 Rn content of mine water was measured by smart radon monitor with bubbler kit. 222 Rn levels of water were well below the limit value of 100 Bq/l. Flow rate of mine water influenced the release of 222 Rn from water to mine air. Contribution of mine water to 222 Rn dose was very low.